2006
DOI: 10.1002/ajmg.b.30326
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the behavioral and neuropsychological correlates of three ADHD candidate gene polymorphisms (DRD4 7+, DBH TaqI A2, and DAT1 40 bp VNTR) in hyperactive and normal children followed to adulthood

Abstract: Several candidate gene polymorphisms have been implicated in attention deficit hyperactivity disorder (ADHD), including DAT1 40bp VNTR, DRD4 7+, and DBH TaqI A2 alleles. We used the Milwaukee longitudinal study of hyperactive (N=122) and normal (N=67) children to compare participants with and without these respective polymorphisms on ADHD-related behavioral ratings at childhood, 8 years later in adolescence, and 13+ years later into young adulthood. Neuropsychological tests were given at the adolescent and you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
1
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 86 publications
9
86
1
3
Order By: Relevance
“…Regarding the genetic analyses, no significant association of SLC6A3 genotype with behavioral data was found. This is in line with the results obtained by Barkley et al (2006) who implemented a similar task, but does not replicate findings by Bellgrove et al (2005) and Loo et al (2003) who report an influence of the 3 0 UTR VNTR on behavioral measures in a Go-NoGo task, especially on response variability. In these previous studies, homozygous 10-repeat allele carriers showed poorer performance and showed greater response time variability than children with at least one nine-repeat allele.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Regarding the genetic analyses, no significant association of SLC6A3 genotype with behavioral data was found. This is in line with the results obtained by Barkley et al (2006) who implemented a similar task, but does not replicate findings by Bellgrove et al (2005) and Loo et al (2003) who report an influence of the 3 0 UTR VNTR on behavioral measures in a Go-NoGo task, especially on response variability. In these previous studies, homozygous 10-repeat allele carriers showed poorer performance and showed greater response time variability than children with at least one nine-repeat allele.…”
Section: Discussionsupporting
confidence: 65%
“…However, Barkley et al (2006) conducted a longitudinal study on children, adolescents, and young adults with ADHD, and report greater ADHD and externalizing symptoms, as well as family, educational, and occupational impairments at all three follow-up examinations in 9/10-as compared with that in 10/10-repeat allele carriers. Also, 9/10-repeat carriers in the control group were prone to higher impairment on educational, occupational, and neurocognitive measures.…”
Section: Introductionmentioning
confidence: 99%
“…The second study showed association between the DRD4 7-repeat allele and worse adult psychosocial outcome [27]. The third study followed 122 ADHD participants and 67 controls across three time points during childhood, adolescence and young adulthood, did not however demonstrate an association between the DRD4 7 repeat allele and ADHD at any time point (although various associations with the DAT1 480 bp VNTR were reported) [4]. Finally, a case-control study of 67 individuals with ADHD found that possession of the 7-repeat allele was associated with better clinical outcome (retaining a diagnosis of combined type ADHD) [32].…”
Section: Discussionmentioning
confidence: 95%
“…Some support for this hypothesis is provided by a prospective 13-year follow-up study indicating that more ADHD symptoms and externalizing behaviors were present in the 9/10 than in the 10/10 genotype for the group as a whole, and that the effects of the genotype became more pronounced with increasing age of the participants. Importantly, more individuals with a DSM diagnosis of ADHD in adulthood were found among those having the 9/10 genotype (53%) than among the 10/10 homozygous group (35%) (Barkley et al, 2006b). On the other hand, as dopamine transporter density decreases during life (Spencer et al, 2005) and ADHD symptoms are known to change during adolescence , the differential association of DAT1 with ADHD might reflect changing requirements on the dopaminergic system during life.…”
Section: Total (95% Ci)mentioning
confidence: 99%